2021
DOI: 10.1038/s41419-021-03964-6
|View full text |Cite|
|
Sign up to set email alerts
|

Absence of Bim sensitizes mice to experimental Trypanosoma cruzi infection

Abstract: Chagas disease is a life-threatening disorder caused by the protozoan parasite Trypanosoma cruzi. Parasite-specific antibodies, CD8+ T cells, as well as IFN-γ and nitric oxide (NO) are key elements of the adaptive and innate immunity against the extracellular and intracellular forms of the parasite. Bim is a potent pro-apoptotic member of the Bcl-2 family implicated in different aspects of the immune regulation, such as negative selection of self-reactive thymocytes and elimination of antigen-specific T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another setting may be pathogen infection, which triggers BAX/BAK activation in a limited number of mitochondria, so-called minority MOMP, to induce STING without caspase activation [439]. Interestingly, loss of BIM prevents pro-inflammatory cytokine production in response to T. cruzi infection in vivo, and induction of PUMA has also been shown to promote cytosolic release of mitochondrial DNA and activation of STING [440,441]. This raises the question of whether BH3-only proteins are also involved in mitochondrial DNA release and STING stimulation through BAX/BAK and MAMs or if they are acting through a separate pathway.…”
Section: The Immuno-mammentioning
confidence: 99%
“…Another setting may be pathogen infection, which triggers BAX/BAK activation in a limited number of mitochondria, so-called minority MOMP, to induce STING without caspase activation [439]. Interestingly, loss of BIM prevents pro-inflammatory cytokine production in response to T. cruzi infection in vivo, and induction of PUMA has also been shown to promote cytosolic release of mitochondrial DNA and activation of STING [440,441]. This raises the question of whether BH3-only proteins are also involved in mitochondrial DNA release and STING stimulation through BAX/BAK and MAMs or if they are acting through a separate pathway.…”
Section: The Immuno-mammentioning
confidence: 99%
“…Moreover, these studies revealed that caspase-8 is also required for CD8 T cell expansion during T. cruzi infection ( 60 ). Finally, Bim-deleted mice are more susceptible to T. cruzi infection, most likely owing to defective macrophage and T cell responses ( 68 ). Therefore, the translation of apoptosis inhibition into treatment for chronic diseases is unlikely so far.…”
Section: Apoptosis Underlies Defective T Cell Help To Macrophages In ...mentioning
confidence: 99%